GEOCHEMICAL MODELING OF EVAPORATION PROCESSES ON MARS: INSIGHT FROM THE SEDIMENTARY RECORD AT MERIDIANI PLANUM - Tosca N.J.; McLennan S.M.; Hurowitz J.A.; Clark B.C.; Grotzinger J.P.; Knoll A.H.; Schröder C.; Squyres S.W. (My University, 2005)
New data returned from the Mars Exploration Rover (MER) mission have revealed abundant evaporites in the sedimentary record at Meridiani Planum. A working hypothesis for Meridiani evaporite formation involves the evaporation of fluids derived from the weathering of martian basalt and subsequent diagenesis. On Earth, evaporite formation in exclusively basaltic settings is rare. However, models of the evaporation of fluids derived from experimentally weathering synthetic martian basalt provide insight into possible formation mechanisms. The thermodynamic database assembled for this investigation includes both Fe2+ and Fe3+ in Pitzer's ion interaction equations to evaluate Fe redox disequilibrium at Meridiani Planum. Modeling results suggest that evaporation of acidic fluids derived from weathering olivine-bearing basalt should produce Mg, Ca, and Fe-sulfates such as jarosite and melanterite. Calculations that model diagenesis by fluid recharge predict the eventual breakdown of jarosite to goethite as well as the preservation of much of the initial soluble evaporite component at modeled porosity values appropriate for relevant depositional environments (< 0.30). While only one of several possible formation scenarios, this simple model is consistent with much of the chemical and mineralogical data obtained on Meridiani Planum outcrop.
Keywords: Mars; Mars exploration rovers; Geochemistry; Evaporites; Weathering; Sulfates